Specialised Language Collocations: A French-English Translation of a Portion of “Protocole National de Prise en Charge de la Malnutrition Aiguë Globale En Haïti” - Taluah, J.W. (University of Ghana, 2020)
This work focuses on Specialised Language Collocations in translating texts from French into English. The source text, “Protocole National de Prise en Charge de la Malnutrition Aiguё Globale en Haїti” [National Protocol for the Management of Global Acute Malnutrition in Haiti] was chosen as a primary source material. Descriptive, analytical and comparative methods were employed in identifying and analysing the similarities and differences between specialised language collocations in a medical text on nutrition, taking into account both linguistic and extra-linguistic factors. The linguistic factors are types of specialised language collocations, transposition, adaptation, adjustment, acronyms, abbreviations, false cognates, polysemy and technical terms. The extra-linguistic factors are text type, professional knowledge and background experience and purpose of the translation. Additionally, translation theories and techniques helped in gaining a better understanding as well as surmounting some challenges encountered in translating the text. The purpose of this study was to delve into specific problems that arise when translating specialised language collocations in order to achieve stylistic and semantic equivalence as this would help convey the intended meaning. Our research establishes that translators who are not native speakers of their working languages, generally, struggle to use appropriate collocations in their translations. Also, this work establishes that even when translators translate into their mother tongues, they struggle to appropriately capture certain collocations, specifically, in the area of nutrition if they do not have enough exposure to materials on nutrition. We can generalise this to mean that translators who do not have adequate knowledge in specific domains may not appropriately render collocations in their translations in those domains. It is hoped that this work would help professional translators whether they are native speakers or non-native speakers of their working languages including those, specifically, with little knowledge in nutrition to be mindful of the said challenges and translate with accuracy and precision.
MA. Translation
Keywords: Specialised language collocations; Acute Malnutrition; Linguistic Factors; Extra- linguistic Factors; Stylistic Equivalence; Semantic Equivalence; Accuracy; Precision